The Production of Activated Carbon from Sago and Pandanus Amaryllifolius - Muhammad Nur Ariff Azhari; Abdul Mutalib Leman; Muhammad Syafiq Muzarpar (Progress in Engineering Application and Technology, 2022)
Activated carbon is one of the most affordable and widely used materials for water purification, cleaning and having been used more recently. Under some condition sorbent tube are used for collecting hazardous gas and to calibrate activated carbon for air sampling tube and it will cause some of disturbance towards efficiency. Objective of the study will go to preparation of the sago and pandanus amaryllifolius as activated carbon. This research will go through pandan and sago as activated carbon and will be test the effectiveness as activated carbon. Method that use to make activated carbon is sago and pandanus amaryllifolius was collected from raw material. Sago and pandanus amaryllifolius will go through process of burning process at 400℃ - 600℃ and activation of carbon shell using KOH, NaOH, H3PO. It will go through crushing process to the size 250-micron filter. After crushing the activated carbon, it will go through sieving process using 50-micron filter. The porosity of activated carbon from each sampling will be determined using Morphology analysis (SEM) analysis and Fourier Transform Infrared Spectroscopy analysis (FTIR). The chemical activation process with KOH was effective in creating well developed pores on the surface of the activated carbon leading produce large porous structures. The use of KOH activating agent produced active carbon’s surface which was smoother. The best activated carbon is using pandanus amaryllifolius with activating agent KOH.